Chapter L'usura tra Santa Croce e Santa Maria Novella: Pietro de Trabibus e Remigio de' Girolami a confronto - LAMBERTINI, Roberto (Reti Medievali E-Book, 2020)
Between 1290 and 1310, two Mendicant friars active in Florence dealt with the controversial issue of usury: the Franciscan lector Peter of Trabibus, who until now has been studied primarily for his relationship to Olivi's teaching, and the Dominican Remigio de' Girolami. In the mid-nineties of the thirteenth century, in the context of his quodlibetal questions, Peter of Trabibus discusses the social role of merchants and he broaches the question of the restitution of usurious gains. Some years later, Remigio also deals with similar issues in his quodlibetal questions and writes a treatise that bears the title De peccato usurae.